Battery Energy Storage System with Fuzzy Logic Control Strategy for Low Voltage Ride-Through Enhancement in Grid Connected Solar Photovoltaic Systems - Aminu, M.; Asogo, I.; Musa, S. Y.; Angeti, J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
This paper presents a battery energy storage system (BESS) integrated with a Fuzzy Logic Control (FLC) to enhance low voltage ride-through (FRT) capability in grid-connected solar photovoltaic (PV) systems during grid disturbances. The increasing penetration of PV systems into modern power grids raises concerns over their reliability and stability under fault conditions. Conventional PV inverters often disconnect during grid faults, compromising grid integrity. To address this problem, a solar PV system integrated with BESS and a Mamdani-type FLC (termed as Fuzzy-BESS) is proposed in this paper. The fuzzy logic controller dynamically managed the energy exchange between the BESS and the grid based on voltage dip severity and the state of charge (SOC) of the battery. The system was subjected to a three-phase-to-ground fault to evaluate its dynamic performance. Simulation results revealed that, without the Fuzzy-BESS, the system experienced severe voltage sags (up to 50% of nominal value) and delayed recovery when subjected to a three-phase-to-ground fault. However, with the integration of Fuzzy-BESS, the system-maintained grid voltage support above ≈88% of nominal value and achieved near-instantaneous recovery (≤0.05 s) after fault clearance. These results confirmed that the proposed Fuzzy-BESS effectively enhanced LVRT capability, improved grid voltage stability, and enabled reliable grid code compliance during fault conditions.